2020
DOI: 10.1017/s1463423620000493
|View full text |Cite
|
Sign up to set email alerts
|

Development of a group-based diabetes education model for migrants with type 2 diabetes, living in Sweden

Abstract: Aim: To develop a diabetes education model based on individual beliefs, knowledge and risk awareness, aimed at migrants with type 2 diabetes, living in Sweden. Background: Type 2 diabetes is rapidly increasing globally, particularly affecting migrants living in developed countries. There is ongoing debate about what kind of teaching method gives the best result, but few studies have evaluated different methods for teaching migrants. Previous studies lack a theoretical base and do not pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 34 publications
0
22
0
1
Order By: Relevance
“…Foreign-born persons reported to a higher degree than Swedish-born that they had sought care due to diabetes mellitus during the last 6 months. The foreign-born persons in this study (Glans et al, 2008); (iii) they had a more information-seeking behaviour, previously found among persons from the Middle East (Hjelm et al, 2003(Hjelm et al, , 2005; (iv) they might have limited or lacking social networks to turn to for advice and that they come from cultures where people are more passive and rely on help from staff (Hjelm et al, 1999;Hjelm et al, 2003) and finally, (v) an indication of insufficient diabetes education, which may be neither individually nor culturally adapted (Hadziabdic et al, 2020). Diabetes care in Sweden is recommended and based on the national guidelines for diabetes care (Socialstyrelsen, 2018), which means that the majority of patients diagnosed with type 2 diabetes are managed in primary healthcare centres mostly by a general practitioner and a diabetes specialist nurse working in mini-teams.…”
Section: Discussionmentioning
confidence: 84%
“…Foreign-born persons reported to a higher degree than Swedish-born that they had sought care due to diabetes mellitus during the last 6 months. The foreign-born persons in this study (Glans et al, 2008); (iii) they had a more information-seeking behaviour, previously found among persons from the Middle East (Hjelm et al, 2003(Hjelm et al, , 2005; (iv) they might have limited or lacking social networks to turn to for advice and that they come from cultures where people are more passive and rely on help from staff (Hjelm et al, 1999;Hjelm et al, 2003) and finally, (v) an indication of insufficient diabetes education, which may be neither individually nor culturally adapted (Hadziabdic et al, 2020). Diabetes care in Sweden is recommended and based on the national guidelines for diabetes care (Socialstyrelsen, 2018), which means that the majority of patients diagnosed with type 2 diabetes are managed in primary healthcare centres mostly by a general practitioner and a diabetes specialist nurse working in mini-teams.…”
Section: Discussionmentioning
confidence: 84%
“…Whether the use of nature cure remedies influences health in persons with diabetes has been studied only to a limited extent. However, as individual beliefs are based on the person's knowledge and guide health-related behaviors, including self-care, it is important to assess them and to plan diabetes education based on individual beliefs about health [7].…”
Section: Discussionmentioning
confidence: 99%
“…The increasing prevalence of type 2 diabetes among migrants, persons who have moved to another country voluntarily as migrants or who have been compelled to move as refugees is well documented and leads to a grave public health task and a challenge for many European countries [5,6]. Language and cultural distance may influence health, self-care practices, education, and the type of healthcare required and provided [7], and make a significant impact on inequalities in diabetes care between persons of minority ethnic origin and the population of origin [5]. Health-related behavior, and thus health, is guided by individual beliefs about health and illness [8][9][10][11][12] that are culturally determined [13].…”
Section: Introductionmentioning
confidence: 99%
“…Direct health education can be done through training programs (Martín-Payo et al ., 2021b); Baptista et al ., 2019), group discussions - Focus Groups Discussion/FGD (Hadziabdic et al ., 2020; Sousa et al ., 2019). Different forms of direct education given to patients is able to increase knowledge, self-care behavior (diet management, physical activity, monitoring blood sugar levels, lower limb/foot care) and self-empowerment.…”
Section: Discussionmentioning
confidence: 99%